The Concept of Anti-Drug Islamic Education For Ma'had Al-Jami'ah Students In Indonesia - Muhlison, Muhlison; Nasution, Wahyudi Nur; Zulkarnain, Zulkarnain (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to analyze in a way deep about the abuse of drugs among maharani. These policies must be adhered to by educators and maharani and concepts of drug Islamic education in Ma'had Al-Jami'ah Indonesia. Methodology The research used by researchers in this research is method study qualitative with a field research approach (research in the field) with descriptive characteristics. As for the results, his research, i.e. [1] Not yet exists Islamic boarding school students who were exposed and caught using drugs when in the institution Ma'had during that one year. Even after they're out of Ma'had, a maharani still avoids and never news about using drugs. To get information about the dangerous drug that is workshop activities at the school level, Mahasantri attended a workshop at the waMa'had campus where the speakers were academics experts, BNN and party police. He also reads online and prints news that can be viewed via his Android cellphone. [2] Providing several Islamic religious materials to maharani in a way scheduled in a year, such as material on the Koran, fiqh, monotheism, tahini, akhlak, tajwid, Arabic and other languages, English. The method used that is lecture, ask-answer, demonstration, modelling, memorization, and story. Activity recommended religion that is Salat congregation, dhikr, reading them and tahlil every Evening Friday, learning to give a speechÂ